2020
DOI: 10.1186/s12913-020-05112-w
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer (CRC) treatment and associated costs in the public sector compared to the private sector in Johannesburg, South Africa

Abstract: Background: South Africa's divided healthcare system is believed to be inequitable as the population serviced by each sector and the treatment received differs while annual healthcare expenditure is similar. The appropriateness of treatment received and in particular the cost of the same treatment between the sectors remains debatable and raises concerns around equitable healthcare. Colorectal cancer places considerable pressure on the funders, yet treatment utilization data and the associated costs of non-com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Although the role of TUG1 in the characteristics and chemoresistance of CRC stem cells is still not well-defined, it has been already presented as an attractive potential biomarker because of its tumor-promotive function via diverse mechanisms, such as RNA-RNA and RNA/transcription factors interactions [ 46 , 84 ]. It was investigated by the same group that TUG1 increased the characteristics and oxaliplatin resistance of CRC stem cells by enhancing GATA6 stability [ 14 ]. TUG1 is suggested to solve the problem of fluoropyrimidine (Fu)-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the role of TUG1 in the characteristics and chemoresistance of CRC stem cells is still not well-defined, it has been already presented as an attractive potential biomarker because of its tumor-promotive function via diverse mechanisms, such as RNA-RNA and RNA/transcription factors interactions [ 46 , 84 ]. It was investigated by the same group that TUG1 increased the characteristics and oxaliplatin resistance of CRC stem cells by enhancing GATA6 stability [ 14 ]. TUG1 is suggested to solve the problem of fluoropyrimidine (Fu)-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the combination of chemotherapy and anti-EGFR (epidermal growth factor receptor) monoclonal antibodies cetuximab and panitumumab can prolong the median survival rate of these patients by 2 to 4 months compared with chemotherapy alone [ 12 ]. However, the impact of these therapies on the 5-year survival remains limited and very expensive [ 13 , 14 ]. Several mutations in oncogenes, tumor suppressor genes, and genes associated with DNA repair have been identified as genetic risk factors for CRCs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“… 112 , 113 Although capecitabine is not widely used in the African public health sector, reports show that it is being used in Nigeria and South Africa, at least. 8 , 114 , 115 …”
Section: Antimetabolitesmentioning
confidence: 99%
“…Resource-stratified guidelines for the treatment of colon cancer patients in low resource settings also recommend adjuvant chemotherapy, but data is sparse on adherence to these guidelines among practitioners. [8][9][10][11] Additionally, a large cohort study of breast cancer patients treated across several public hospitals in ZA showed that 25% of eligible patients do not initiate adjuvant systemic therapy, despite availability at low or no cost. 12 This data, despite being in a different tumor, suggest that adjuvant chemotherapy uptake is likely suboptimal in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…Post‐surgery adjuvant chemotherapy is standard of care for patients with high‐risk stage II and those with stage III colon cancer (CC) in high‐income countries (HICs). Resource‐stratified guidelines for the treatment of colon cancer patients in low resource settings also recommend adjuvant chemotherapy, but data is sparse on adherence to these guidelines among practitioners 8–11 . Additionally, a large cohort study of breast cancer patients treated across several public hospitals in ZA showed that 25% of eligible patients do not initiate adjuvant systemic therapy, despite availability at low or no cost 12 .…”
Section: Introductionmentioning
confidence: 99%